1989
DOI: 10.1002/aja.1001860108
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of endoplasmic reticulum in rapidly dividing cells of early Xenopus embryos

Abstract: The cytology of early blastomeres of Xenopus laevis embryos was examined. Particular attention was given to the organization of the nuclear envelope of karyomeres (chromosome vesicles) and the endoplasmic reticulum (ER) at different stages in early cleavage cycles of frog development. Nuclear envelope formation was observed to occur rapidly around individual chromosomes during early anaphase, and karyomeres fused subsequently to yield the final nucleus during telophase. Endoplasmic reticulum in the perinuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Although previous studies clearly indicated microtubule-dependent formation of ER networks in vivo (Terasaki et al, 1986;Lee and Chen, 1988), we were unable to confirm such a relationship in our studies. Neither vinblastine nor nocodazole used at concentrations previously shown to inhibit other microtubule-dependent processes in both Xenopus oocytes and eggs Dominguez and Paiement, 1989) were able to prevent initiation of formation or maintenance of the reconstituted ER network in the present study. Perhaps ER network formation in Xenopus oocytes is microtubuleindependent and, in this sense, resembles more ER network formation in characean algal cells (Kachar and Reese, 1988).…”
Section: N V I V Ocontrasting
confidence: 51%
See 3 more Smart Citations
“…Although previous studies clearly indicated microtubule-dependent formation of ER networks in vivo (Terasaki et al, 1986;Lee and Chen, 1988), we were unable to confirm such a relationship in our studies. Neither vinblastine nor nocodazole used at concentrations previously shown to inhibit other microtubule-dependent processes in both Xenopus oocytes and eggs Dominguez and Paiement, 1989) were able to prevent initiation of formation or maintenance of the reconstituted ER network in the present study. Perhaps ER network formation in Xenopus oocytes is microtubuleindependent and, in this sense, resembles more ER network formation in characean algal cells (Kachar and Reese, 1988).…”
Section: N V I V Ocontrasting
confidence: 51%
“…Both these agents were shown to lead to cleavage arrest in early developing Xenopus embryos (Dominguez and Paiement, 1989). Furthermore vinblastine was shown to induce pigment dispersion and the formation of tubular crystalloids in Xenopus oocytes .…”
Section: Effect Of Microtubule Inhibitors On the Formation And Maintementioning
confidence: 98%
See 2 more Smart Citations
“…However, in cleaving blastomeres of some echinoderm (24,28,34,37,40) and amphibian embryos (8,26), chromosome cycles continue if…”
Section: Introductionmentioning
confidence: 99%